PPI efficacy in the reduction of variceal bleeding incidence and mortality, a meta-analysis - Sheref A. Elseidy; Ahmed Sayed; Ahmed K. Awad; Debvarsha Mandal; Mariam Mostafa; Aisha Adigun; Monica Vorla; Zarlakhta Zamani; Amir Iqbal (SpringerOpen, 2022)
Abstract Objective To review the efficacy and safety of proton pump inhibitors (PPIs) in gastroesophageal varices (GEVs). Methods We searched PubMed MEDLINE, Scopus, and Web of Science for studies that measured the effect of PPI for prophylaxis and treatment of post-band ligation ulcers up to July 20, 2021. We included studies that measured the effect of PPI as treatment or prophylaxis for post-band ligation ulcers; articles that were published in peer-reviewed international journals and had enough data for qualitative and quantitative analysis were included with no language restriction. Heterogeneity was evaluated using the inconsistency (I 2) and chi-squared (χ 2) test. I 2 > 50% was considered substantial heterogeneity in the studies, and a P value less than 0.05 was considered statistically significant. The data was continuous, and we used the standardized mean difference (MD) and risk ratio (RR) with a 95% confidence interval to assess the estimated effect measure. Results A total of 7 studies with 2030 patients were included in our study of which 1480 participants were males (72%) and 550 females (18%). Mean age was 59.7 years old. Rebleeding post-band ligation was compared between PPI and placebo with significant favor for PPI (p = 0.00001). The pooled risk ratio was 0.53 (95% CI of 0.41, 0.68); furthermore, bleeding-related death at a 1-month period was compared between PPI and placebo with significant favor for PPI (p = 0.00001). The pooled risk ratio was significant at 0.33 (95% CI of 0.20, 0.53). The length of hospital stay postoperative was compared between PPI and placebo with cumulative mean difference of 0.13 (95% CI of −1.13, 1.39), yet without significance. Conclusions The study suggests a twofold reduction in the risk of bleeding and a threefold reduction in the risk of bleeding-related death with the use of PPI following EVL.